Performance of Pervious Concrete Containing KENAF Fiber - Teo, Meng Jie (2017)
This study objective is to find the adding of Kenaf Fiber content will result in affect the mechanical properties of pervious concrete. In this study, the mechanical properties study includes are compressive strength, split tensile strength, flexural tensile strength and pemeability. Besides that, sieve analysis was conducted to study the consistent of the grain size distribute. Since the aggregate size use on a pervious concrete is a key which affect the mechanical properties. Through study, 0.1% of the kenaf fiber might be the optimum percentage of kenaf fiber to improve the split tensile strength. The split tensile strength had improved 11.23% with added of 0.1% content of kenaf Fiber into concrete mix. The 0.1% content of kenaf fiber has a high rate of 6.29 l/min of the permeability